1975
DOI: 10.1016/0031-9384(75)90115-8
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Pavlovian conditioned cardiodecelerations following preshock in immobilized rats☆

Abstract: Facilitation of Pavlovian conditioned cardiodecelerations following preshock in immobilized rats. PHYSIOL. BEHAV. 15(6) 653-658, 1975. -Two experiments are reported that examine the effects of unsignalled, inescapable prior shock exposure (PSE) on shock-motivated Pavlovian conditioned heart rate (HR) decelerations in rats. Both studies involved 2 CS-US contingencies (paired and unpaired) and 2 preshock treatments (preshock and no preshock). The 2 designs differed in the type of immobilization procedures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Studies in both humans and experimental animals have found that high endogenous baseline levels or exogenous administration of cortisol or stress prior to a memory task is associated with better immediate performance, implying beneficial effects on memory acquisition or encoding (Wilson et al 1975;Beckwith et al 1986;Shors et al 1992;Fehm-Wolfsdorf et al 1993;Bemelsmans et al 2002;Domes et al 2002;Lupien et al 2002a,b;Abercrombie et al 2003;Akirav et al 2004;Putman et al 2004;Maheu et al 2005b;Zorawski et al 2005). However, the issue is not unequivocal, and contradictory results have been reported (Wolkowitz et al 1990;Kirschbaum et al 1996;Lupien et al , 1999Wolf et al 2001a,b;Maheu et al 2004).…”
mentioning
confidence: 80%
“…Studies in both humans and experimental animals have found that high endogenous baseline levels or exogenous administration of cortisol or stress prior to a memory task is associated with better immediate performance, implying beneficial effects on memory acquisition or encoding (Wilson et al 1975;Beckwith et al 1986;Shors et al 1992;Fehm-Wolfsdorf et al 1993;Bemelsmans et al 2002;Domes et al 2002;Lupien et al 2002a,b;Abercrombie et al 2003;Akirav et al 2004;Putman et al 2004;Maheu et al 2005b;Zorawski et al 2005). However, the issue is not unequivocal, and contradictory results have been reported (Wolkowitz et al 1990;Kirschbaum et al 1996;Lupien et al , 1999Wolf et al 2001a,b;Maheu et al 2004).…”
mentioning
confidence: 80%
“…response (Wilson et al 1975). Interestingly, we have not observed enhancing effects of this type of stressor on classical fear conditioning using a decrease in movement as the measure of performance (D.A.…”
Section: Stress and Classical Conditioningmentioning
confidence: 99%
“…The acquisition of a conditioned response during aversive learning in rodents, for example, has been shown to be enhanced in males under stress (Wilson et al, 1975; Shors et al, 1992) and depressed in females under stress (e.g., Wood and Shors, 1998; Wood et al, 2001). This is highly context dependent, however, as factors such as stressor type (e.g., swim stress, noise or restraint; Shors, 2001) and the temporal proximity of the learning process to the experienced stress (see Joëls et al, 2006 for review) can affect the manner in which stress alters learning.…”
Section: Introductionmentioning
confidence: 99%